Fingolimod for the treatment of neurological diseases—state of play and future perspectives - Brunkhorst, Robert; Vutukuri, Rajkumar; Pfeilschifter, Waltraud (Frontiers in Cellular Neuroscience, 2014)
Sphingolipids are a fascinating class of signaling molecules derived from the membrane lipid sphingomyelin. They show abundant expression in the brain. Complex sphingolipids such as glycosphingolipids (gangliosides and cerebrosides) regulate vesicular transport and lysosomal degradation and their dysregulation can lead to storage diseases with a neurological phenotype. More recently, simple sphingolipids such ceramide, sphingosine and sphingosine 1-phosphate (S1P) were discovered to signal in response to many extracellular stimuli. Forming an intricate signaling network, the balance of these readily interchangeable mediators is decisive for cell fate under stressful conditions. The immunomodulator fingolimod is the prodrug of an S1P receptor agonist. Following receptor activation, the drug leads to downregulation of the S1P1 receptor with the consequence of functional antagonism. Being the first drug to modulate the sphingolipid signaling pathway, it was marketed in 2010 for the treatment of multiple sclerosis (MS). At that time, immunomodulation was widely accepted as the key mechanism of fingolimod's efficacy in MS. But given the excellent passage of this lipophilic compound into the brain and its massive brain accumulation as well as the abundant expression of S1P receptors on brain cells, it is conceivable that fingolimod also affects brain cells directly. Indeed, a seminal study showed that the protective effect of fingolimod in experimental autoimmune encephalitis (EAE), a murine MS model, is lost in mice lacking the S1P1 receptor on astrocytes, arguing for a specific role of astrocytic S1P signaling in multiple sclerosis. In this review, we discuss the role of sphingolipid mediators and their metabolizing enzymes in neurologic diseases and putative therapeutic strategies arising thereof.